2021
DOI: 10.7759/cureus.20545
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Venous Excess Ultrasound Score (VExUS) to Guide Decongestion in a Dilated Cardiomyopathy Patient Presenting for Urgent Surgery

Abstract: Venous excess ultrasound score (VExUS) is a recently described ultrasound-based scoring system that quantifies systemic congestion using Doppler flow indices of the hepatic and portal vein in addition to inferior vena cava assessment. There are many potential and emerging applications of this modality. We discuss the case of a severely congested heart failure patient presenting for urgent non-cardiac surgery where VExUS parameters were used to monitor and guide his decongestive therapy postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The use of bedside Doppler ultrasonography to measure VRS may be effective for evaluating organ perfusion, assessing the hemodynamic response to fluid administration [ 59 , 60 ], detecting RVD, and predicting outcomes in critically ill patients, including occurrence of AKI [ 15 , 29 ], length of hospital stay, and mortality [ 7 ]. Bedside ultrasonography can guide treatment and be used to monitor the effects of diuretic therapy [ 61 ]. Although case reports have suggested the potential benefits of dynamically monitoring venous reflux disorders to improve patient outcomes, there is a scarcity of prospective randomized controlled studies in this field.…”
Section: Discussionmentioning
confidence: 99%
“…The use of bedside Doppler ultrasonography to measure VRS may be effective for evaluating organ perfusion, assessing the hemodynamic response to fluid administration [ 59 , 60 ], detecting RVD, and predicting outcomes in critically ill patients, including occurrence of AKI [ 15 , 29 ], length of hospital stay, and mortality [ 7 ]. Bedside ultrasonography can guide treatment and be used to monitor the effects of diuretic therapy [ 61 ]. Although case reports have suggested the potential benefits of dynamically monitoring venous reflux disorders to improve patient outcomes, there is a scarcity of prospective randomized controlled studies in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Another study of 33 critically-ill children showed a significant correlation between VExUS grade and CVP [50 ▪ ]. There has been only one case report in the surgical literature, describing the successful use of VExUS for decongestion of a patient with congenital cardiomyopathy [51]. A recent case series reviewed the rationale and supporting evidence for broader application of VExUS in a variety of clinical settings [52].…”
Section: Venous Excess Ultrasound ‘Vexus’ Gradesmentioning
confidence: 99%
“…A potential limitation of VExUS is its use in chronic liver disease wherein low hepatic pulsatility can be present even with significant systemic congestion. In the perioperative setting, this can help guide decongestive therapy in patients with heart failure, facilitate the management of right ventricular dysfunction, and potentially reduce the risk of postoperative acute kidney injury and pulmonary edema 87,91,92 .…”
Section: Venous Excess Ultrasound Score (Vexus)mentioning
confidence: 99%